Mortality differentials by religious denomination in Vienna 1981-2002 - Johannes Klotz; Richard Gisser (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
Using statistical record linkage of anonymized population census data 1981, 1991 and 2001 with deaths during twelve months from census day, we computed standardized mortality ratios for nine religious groups (including groups with no religion and religion not stated) in the city of Vienna. Relative mortality risk is above average for Roman Catholics (1.01), but below average for Protestants (0.98) and people with no religion (0.97). Very low mortality risks are found for Muslims and Orthodox Christians, which is partly due to the low mortality of foreign immigrants. The lower mortality risk of Protestants compared to Roman Catholics is restricted to males and essentially due to different educational distributions. Despite their low overall mortality level, people with no religion face excess suicide mortality.
Keywords: 300; Vienna; mortality; standardized mortality ratio; life expectancy; religion; suicide